A Social Critique of Behavioral Approaches to International Law. (20th July 2021) - Cho, Sungjoon
Abstract : Behavioral approaches have been successful in challenging the rational actor model of international legal analysis and supplementing that model with empirical evidence. Yet observing a set of features about the world requires ignoring or bracketing others. Behavioral approaches retain their own inevitable blind spots, which are not necessarily products of flawed experimental design, but stem from the paradigmatic traits of these approaches. These blind spots derive from an emphasis on methodological individualism, positivism, and experimentation. This emphasis may obscure the social aspects of international legal decision-making. For example, behavioral approaches to international law often use experimental data to describe cognitive tendencies. In doing so, these approaches may not seek and likely will not have tools to discover the meaning of a state action, or the human actions that produce that state action. That latter inquiry requires "historical, ethnographic and other sociological methods that analyze social life outside of the experimental setting." In sum, behavioral approaches pursue both theoretical and empirical concerns different from those pursued in an interpretive mode of meaning-making.